Preparasi Imunoglobulin G Kelinci sebagai Antigen Penginduksi Antibodi Spesifik Terhadap Virus Avian Influenza H5N1 Strain Legok - Karuni Nyanakumari Natih, Ketut; Damayanti Soejoedono, Retno; Teguh Wibawan, I Wayan; Hasmi Pasaribu, Fachriyan (Jurnal Veteriner; Vol 11 No 2 (2010), 2010)
The aim of this research was to prepare rabbit Immunoglobulin G as anti-idiotype antibody (Ab2) ofAvian Influenza Virus (AIV) H5N1. A polyclonal antibody was collected from guinea pigs immunized withinactivated AI vaccine H5N1of Legok strain. Antibody of H5N1 AI in serum was detected by Agar gelprecipitation test (AGPT) and an Inhibition Hemmaglutination test (IHT). The highest titre of antibodywas obtained one week after the third immunization. Serum of guinea pigs containing IgG was purifiedusing the Montage Antibody purification kit & spin column with Prosep A media (Millipore). The AI H5N1IgG concentration was 8 mg/ml. AI H5N1 IgG, was then digested with pepsin to obtain F(ab)2 fraction andwas called Ab1. The concentration of IgG and F(ab)2 and purity of IgG were determined by UVspectrophotometer which showed Ab1 concentration 1 mg/ml. Molecular weight was estimated by sodiumdodecyl sulfate- polyacrilamide gel electrophoresis (SDS-PAGE). Ab2 was produced by immunization ofrabbit with Ab1. The first immunization was carried out by subcutaneous injection with 500 ?g of Ab1emulsified in Complete Freund Adjuvant. The immunization was repeated with the same dose of Ab1emulsified in Incomplete Freund Adjuvan at 1 week intervals. One week after the second immunization,rabbit’s serum was harvested and IgG was purified using the Montage Antibody purification kit & spincolumn with Prosep A media (Millipore). The rabbit IgG, called Ab2, was an anti-idiotypic antibody againstAIV-H5N1. In AGPT, a precipitation line appeared between Ab1 and Ab2. A partial reaction appearedbetween Ab2 and the AI H5N1 antigen was also detected. The results indicated that Ab2 is a possiblecandidate of imunogen for protection against an AI virus H5N1 infection.
Keywords: Avian Influenza, Immunoglobulin G (IgG), anti-idiotype antibody